2021
DOI: 10.3390/educsci11040173
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of University STEM Students’ Mathematical, Linguistic, Rhetorical–Organizational Assignment Errors

Abstract: Although Error Analysis (EA) has been broadly used in Foreign Language and Mother Tongue learning contexts, it has not been applied in the field of engineering and by STEM (Science, Technology, Engineering, and Mathematics) students in a systematic way. In this interdisciplinary pilot study, we applied the EA methodology to a wide corpus of exercises and essays written by third-year students of mechanical engineering, with the main purpose of achieving a precise diagnosis of the students’ strengths and weaknes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
0
8
0
3
Order By: Relevance
“…21 Arevalo et al, note that some of the inadequacies which the STEM students faced were their linguistic and reporting skills, which would have been alleviated by comprehensive consultation in physical classes. 22 In the study of Zis et al, medical students also faced difficulty in coping with the lockdown as their learning patterns were disrupted and they felt overwhelmed with the increasing burden in keeping up with their studies. 23 Measures, such as virtual learning, have been implemented to ensure educational continuity in the wake of system disruption.Many people believe that virtual learning is more beneficial than it actually is.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21 Arevalo et al, note that some of the inadequacies which the STEM students faced were their linguistic and reporting skills, which would have been alleviated by comprehensive consultation in physical classes. 22 In the study of Zis et al, medical students also faced difficulty in coping with the lockdown as their learning patterns were disrupted and they felt overwhelmed with the increasing burden in keeping up with their studies. 23 Measures, such as virtual learning, have been implemented to ensure educational continuity in the wake of system disruption.Many people believe that virtual learning is more beneficial than it actually is.…”
Section: Discussionmentioning
confidence: 99%
“…From 1 (never) to 5 (always), participants rated their level of agreement with each of the 10 statements on a 5-point Likert-type scale. Each score was classified as mild (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), moderate (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), high (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45), or severe (45-50) based on the maximum possible score. A content validity of 0.91 and test-retest reliability of 0.93 were found for the scale's content validity.…”
Section: Lockdown Fatigue Scalementioning
confidence: 99%
See 1 more Smart Citation
“…The study concluded that it is important to give primary focus on strategies in reviewing the literature as such can help students review relevant research and establish the research problem. Arévalo et al (2021) provided a comprehensive error analysis of STEM students' mathematical, linguistic, and rhetorical-organizational assignments. The result showed that the dominant errors were rhetorical-organizational (39%) and linguistic (38%).…”
Section: Empirical Studies On the Structure Of Research Introductions...mentioning
confidence: 99%
“…Furthermore, by integrating natural sciences, technology, engineering, and mathematics, these methodologies enable students to acquire theoretical and practical knowledge in critical areas, foster collaboration, innovation, and creativity, and prepare students for a career in engineering. (Arévalo, Cantera, García-Marina, & Alves-Castro, 2021) This paper reviews ten scientific articles on the importance of STEM methodologies for engineering education to know the fundamental elements necessary in training the new engineers of the future. The industrial future is envisioned with high digital and multidisciplinary content, so engineering schools must reform their curricula so that new professionals have a new vision of their participation in modern industry.…”
mentioning
confidence: 99%